Alopecia Areata Incognita and Diffuse Alopecia Areata: Clinical, Trichoscopic, Histopathological, and Therapeutic Features of a 5-Year Study - Aurora Alessandrini; Michela Starace; Francesca Bruni; Nicolò Brandi; Carlotta Baraldi; Cosimo Misciali; Pier Alessandro Fanti; Bianca Maria Piraccini (Dermatology Practical & Conceptual, 2019)
Background: Alopecia areata is a nonscarring hair loss that usually causes round patches of baldness, but alopecia areata incognita (AAI) and diffuse alopecia areata (DAA) can cause a diffuse and acute pattern of hair loss.